Crop-livestock interaction in sub-Saharan Africa - McIntire, John M.; Bourzat, D.; Pingali, Prabhu L. (World Bank, 1992)
Describes interactions between cropping & livestock husbandry in an area of Fulani settlement arid farming groups at Abet and in a Fulani agropastoral system at Kurmin Biri, both in subhumid Nigeria, identifying the linkages as being feed from fallow land crop residues (CR) grazing and use of cattle manure in cropping w. data on biomass production on a fallow land; quantity & nutritive value of CR grazing arrangements and relative contributions of CR to cattle diets; and seasonal differences in quality & quantity of manures and changes in crop yield, weed infestation & soil properties w. manuring in the two study areas.